MENINGKATKAN MAAJEMEN KEUANGAN UMKM : DAMPAK FINANCIAL KNOWLEDGE, LOVE OF MONEY, DAN SELF-EFFICACY - Regita Putri Cahyani; zaki; Moh. Zaki Kurniawan; Helmi Buyung Aulia Safrizal (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2025)
Madura is an island in Indonesia that is rich in diversity. Madura's diversity can innovate in the development of traditional businesses, the difficulties that exist in Madura. However, there are several obstacles that UMKM in Madura often face. These obstacles, such as marketing which is still generally traditional, difficulty accessing financial services, can make UMKM players tend not to understand how to manage UMKM finances properly and correctly. The research objective is to determine the influence of financial knowledge, love of money, and financial self-efficacy on the financial management of Madurese MSMEs. The population is MSME actors in sub-districts in Sampang district, with a sample of 100 MSME actors in Sampan district. Quantitative research is used by researchers as a type of research, where data is collected through questionnaires and interviews with multiple linear analysis and classical assumption analysis. The results explain that financial knowledge, love of money, and financial self-efficacy have a positive and significant influence on the financial management of MSMEs in Madura. This research provides the implication that increasing financial knowledge and self-confidence in financial management can improve the quality of financial management of MSMEs in Sampang district.